2007
DOI: 10.2164/jandrol.106.000810
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Expression in Human Testis and Serum Testosterone Level

Abstract: Ghrelin, which is the endogenous ligand for the growth hormone (GH) secretagogue receptor (GHS-R), has been primarily linked to the central neuroendocrine regulation of GH secretion and food intake, although additional peripheral actions of ghrelin have also been reported. Recent research has suggested that ghrelin also affects testosterone (T) secretion in vitro. To investigate the role of ghrelin in human testicular function, we examined the expression of ghrelin in testicular tissues by immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 28 publications
4
44
0
6
Order By: Relevance
“…In2c-ghrelin is expressed in all normal testis samples examined, while it is expressed in a small number of testicular tumours. This correlates well with previous studies, which have shown that the ghrelin peptide is present in normal human testis (Gaytan et al 2004, Ishikawa et al 2007) and in a subset of testicular tumours (Gaytan et al 2004). Employing a small number of normal samples, we also demonstrate that in2c-ghrelin is expressed in breast and ovarian tumours but not in normal breast or ovary.…”
Section: Discussionsupporting
confidence: 92%
“…In2c-ghrelin is expressed in all normal testis samples examined, while it is expressed in a small number of testicular tumours. This correlates well with previous studies, which have shown that the ghrelin peptide is present in normal human testis (Gaytan et al 2004, Ishikawa et al 2007) and in a subset of testicular tumours (Gaytan et al 2004). Employing a small number of normal samples, we also demonstrate that in2c-ghrelin is expressed in breast and ovarian tumours but not in normal breast or ovary.…”
Section: Discussionsupporting
confidence: 92%
“…Duran et al [41] demonstrated decreased serum Ghrelin levels in idiopathic hypogonadotropic hypogonadism (IHH) patients who also had lower serum LH and testoste- [42] demonstrated that when the serum testosterone levels were increased, serum ghrelin level was increased significantly. Ishikawa et al [43] demonstrated that expression of ghrelin by Leydig cells is inversely correlated with the serum T concentration. Also they have proposed that ghrelin has not directly related on spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In human spermatogenic cells, especially in pachytenes, they localized GHSR-1a protein. Controversially, other researchers demonstrated ghrelin immunohistochemically in pachytene spermatocytes of human [36] and ovine testis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatocytes in human, rat and ovine testis expressed ghrelin and GHSR-1a and authors suggested that ghrelin can influence spermatogenesis acting via Leydig cells and may operate as a local regulator in the fine-tuning of spermatogenic function [36], however, without exception of the possibility that ghrelin may regulate gene expression of local modulators in the rat seminiferous tubules [32,34]. Appreciating the above novel data reflecting role of the peptide and its receptor in control of male gonad function via Leydig cells we intend to consider the gathered results of own studies in light of the local regulatory mechanism for the course of spermatogenesis within the cycle of seminiferous epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation